Balancing the Multi Assembly line Using Ranked Positional Weight and COMSOAL Algorithms: Case Study at the Sewing line Factory (7) /the General Company for Leather Industries (GCLI/ Baghdad) - النجار صباح مجيد; ماجود هالة حمد (Journal of Economics and Administrative Sciences, 2013)
The problem of multi assembly line balancing appears as one of the most prominent and complex type of problem. The research problem of this dissertation is concerned with choosing the suitable method that includes the nature of the processes of the multi assembly type of the sewing line at factory no. (7). The State Company for Leather Manufacturing. The sewing line currently suffers from idle times at work stations which resulted in low production levels that do not meet the production plans. The authors have devised a flexible simulation model which uses the uniform distribution to generate task time for each shoe type produced by the factory. The simulation of the multi assembly line was based on assigning task times to work stations according to two heuristics (Ranked positional Weight and COMSOAL). Performance measures were computed and were used to test the three research hypothesis. The research has reached a number of conclusions that have proved the validity of the simulation model to address the research problem, and to achieve the balance of the sewing line. It is quite clear that the applied algorithms have effective impact on achieving better results to improve the line’s efficiency and to maximize its output in comparison with the actial performance of the line. The authors recommend the application of the simulation model developed here to study the problems of the multi assembly line.